STRATEGI PEMBERDAYAAN EKOWISATA MELALUI MANGROVE LAMPUNG CENTER (MLC) INOVASI STRATEGIS DALAM AGENDA PEMBANGUNAN EKONOMI PEMERINTAH DAERAH - Septinda, Fera; Kartika, Tina; Fera Septinda; Tina Kartika (JURNAL TAPIS, 2023)
Ecotourism empowerment through mangroves is not yet optimal in Margasari Village, Labuhan Maringgai District, East Lampung Regency even though it is known to have great potential in increasing economic value for the local community. With the presence of MLC as a mangrove conservation center that focuses on environmental education and ecotourism activities. The aim of this research is to evaluate the impact of ecotourism empowerment through MLC on increasing the economic value of the community in Margasari Village. The research method used in this study is observation and interviews with the local community. Through the development of ecotourism attractions such as mangrove exploration and planting mangrove seedlings, MLC has succeeded in attracting tourist visits which has an impact on increasing the income of local communities. Apart from that, empowering ecotourism also provides job opportunities for the community. MLC involves local communities in tourism management and services, such as being tour guides and food stall managers. This not only increases their income, but also provides an opportunity to develop skills and knowledge about the environment. However, there are still several challenges that need to be overcome. Among them, improving supporting infrastructure, such as better road access and adequate sanitation facilities. Apart from that, education and environmental awareness also need to be improved so that people can preserve mangroves and their ecosystems.